2021
DOI: 10.3390/cancers13020341
|View full text |Cite
|
Sign up to set email alerts
|

The Giant HECT E3 Ubiquitin Ligase HERC1 Is Aberrantly Expressed in Myeloid Related Disorders and It Is a Novel BCR-ABL1 Binding Partner

Abstract: HERC E3 subfamily members are parts of the E3 ubiquitin ligases and key players for a wide range of cellular functions. Though the involvement of the Ubiquitin Proteasome System in blood disorders has been broadly studied, so far the role of large HERCs in this context remains unexplored. In the present study we examined the expression of the large HECT E3 Ubiquitin Ligase, HERC1, in blood disorders. Our findings revealed that HERC1 gene expression was severely downregulated both in acute and in chronic myelog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
3
4
0
Order By: Relevance
“…However, their role in nonsolid tumors has started to be explored quite recently. In our previous study, we reported an association of HERC1 gene expression with some myeloid-related disorders [20]. Curiously, besides our findings, the knowledge regarding the other large HERC sub-family member, HERC2, is currently missing in blood malignancies.…”
Section: Herc2 Gene Expression Is Severely Down-modulated In CML Specimens But Returns To Normal Levels Upon Remissionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, their role in nonsolid tumors has started to be explored quite recently. In our previous study, we reported an association of HERC1 gene expression with some myeloid-related disorders [20]. Curiously, besides our findings, the knowledge regarding the other large HERC sub-family member, HERC2, is currently missing in blood malignancies.…”
Section: Herc2 Gene Expression Is Severely Down-modulated In CML Specimens But Returns To Normal Levels Upon Remissionsupporting
confidence: 62%
“…Overall, it is likely that BCR-ABL exerts a negative effect on the accumulation of these HERC genes. Recently, we observed that BCR-ABL interacts with HERC1 and that the latter is a substrate of the former [20]. Determining the molecular mechanism/s by which large HERCs are downregulated in CML and ascertaining to what levels the aberrant HERCs transcripts dysregulation occurs will be a matter of future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, though very rare, an atypical HERC1-PML transcript fusion mRNA has been described in APL, though the functional outcome of this chimera has not been yet investigated [ 93 ]. Ali and collaborators [ 94 ] have recently reported that HERC1 expression is dysregulated in myeloid related neoplasms. At diagnosis, HERC1 transcript levels are markedly down-regulated in AML, CML and primary myelofibrosis, an aggressive form of myeloproliferative neoplasm (MPN), relatively to bone marrow and peripheral blood control cells.…”
Section: Role Of the Hect E3s In The Pathogenesis Of Leukemiamentioning
confidence: 99%
“…MPNs include polycythemia vera, essential thrombocythemia, and primary (idiopathic) myelofibrosis. MPN patients can spontaneously transform into either myelodysplastic syndrome or AML Somatic mutations (JAK2, calreticulin, thrombopoietin receptor 2,17 HERC1 [ 94 ] …”
Section: Introductionmentioning
confidence: 99%